2009
DOI: 10.1097/wnr.0b013e328332bb09
|View full text |Cite
|
Sign up to set email alerts
|

Chronic stress selectively reduces hippocampal volume in rats: a longitudinal magnetic resonance imaging study

Abstract: The notion of uncontrollable stress causing reduced hippocampal size remains controversial in the posttraumatic stress disorder literature because human studies cannot discern the causality of effect. Here, we addressed this issue by employing structural magnetic resonance imaging in rats to measure the hippocampus and other brain regions before and after stress. Chronic restraint stress produced approximately 3% reduction in hippocampal volume, which was not observed in control rats. This decrease was not sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
94
3
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(111 citation statements)
references
References 24 publications
12
94
3
2
Order By: Relevance
“…Interestingly, exposure to chronic stress during adulthood can lead to a reduction in hippocampal volume if the stress is severe and prolonged enough [(Pham et al, 2003;for review, see Sapolsky (2000)]. For example, using structural magnetic resonance imaging, chronic restraint stress decreases hippocampal volume by 3% in adult male rats (Lee et al, 2009). Thus, the ability of chronic stress to decrease hippocampal volume is dependent on a number of variables including developmental time of exposure, amount of stress and stressor type.…”
Section: Exposure To Chronic Stress During Adolescence Alters Hippocamentioning
confidence: 98%
“…Interestingly, exposure to chronic stress during adulthood can lead to a reduction in hippocampal volume if the stress is severe and prolonged enough [(Pham et al, 2003;for review, see Sapolsky (2000)]. For example, using structural magnetic resonance imaging, chronic restraint stress decreases hippocampal volume by 3% in adult male rats (Lee et al, 2009). Thus, the ability of chronic stress to decrease hippocampal volume is dependent on a number of variables including developmental time of exposure, amount of stress and stressor type.…”
Section: Exposure To Chronic Stress During Adolescence Alters Hippocamentioning
confidence: 98%
“…Here, further research is needed to address the question of comparability between histological and MRI lesion quantification. We chose MRI scans for analyzing lesion extent, because (a) hippocampal damage can be directly measured in the living animal, (b) the brains are not affected by perfusion, brain removal, cutting, and staining and (c) the method has been used by other researchers to validate hippocampal lesions (Lee et al, 2009). On the other hand, it has to be mentioned that (a) the histological analyses are more precise-i.e., the contours, especially of the hippocampus, are better visible histologically-and (b) the injection tracts appear clearly bigger in the MRI scans, due to susceptibility artifacts around the needle tracts (see images of the sham operated animal in Fig.…”
Section: Mri Analysesmentioning
confidence: 99%
“…During scanning, rats were anesthetized with Isofloran (Baxter GmbH, Unterschleibheim, Germany). For lesion validation we used images with the following parameters (similar to Lee et al, 2009): repetition time (TR) 5 3,000 ls; echo time (TE) 5 31 ls; number of slices 5 17; slice thickness 5 0.7 mm; field of view (FoV) 5 40 3 40 mm 2 ; matrix 5 320 3 320; final spatial resolution 5 0.125 3 0.125 3 0.7 mm 2 . The first coronal slices started from approximately 28.0 mm from bregma and ended at approximately 12.27 according to the atlas by Paxinos and Watson (2007).…”
Section: Mri Analysesmentioning
confidence: 99%
“…In particular, and with significant clinical implications, human brain imaging studies have reported that PTSD patients had smaller hippocampal volume, which correlated with deficits in verbal memory (e.g., Bremner et al 1995). Although a subsequent monozygotic twin study has suggested that reduced hippocampal volume is a predisposing factor for the development of PTSD following trauma (Gilbertson et al 2002), a recent longitudinal MRI study in rats demonstrated that chronic restraint stress does cause a reduction in hippocampal volume from the prestress size (Lee et al 2009). These effects are likely mediated by stress effects on neuronal morphology and/or neurogenesis in the hippocampus.…”
Section: Stress Effects On Hippocampal Morphologymentioning
confidence: 99%